3D MR neurography with gadolinium contrast to improve the visualization of pelvic nerves and the branches - Liu, Hui; Xiao, Zhibo; Tao, Li; Tang, Mingmei; Xu, Yong; Pan, Yuanrui; Zhang, Ke; Qiu, Xueke; Lv, Fajin (Frontiers in Physiology, 2024)
Objective: To evaluate the effectiveness of 3D NerveVIEW sequence with gadolinium contrast on the visualization of pelvic nerves and their branches compared to that without contrast. Methods: Participants were scanned twice using 3D NerveVIEW sequence with and without gadolinium contrast to acquire pelvic nerve images. The signal-to-noise ratio (SNR), contrast-tonoise ratio (CNR) and contrast ratio (CR) of the nerves were calculated and compared to determine the quality of images. To subjectively assess, using a 3-point scale, branch nerves critical to therapeutic decision-making, including the pelvic splanchnic nerve and pelvic plexus, the superior gluteal nerve, and the pudendal nerve.Results: In the 32 eligible participants after using contrast, the CNRs of the images of nerve-to-bone and nerve-to-vessel significantly increased (p<0.05). The CR of the images with contrast of all nerveto-surrounding tissues (i.e. bone, muscle, blood vessels, and fat) were also found significantly higher (p<0.05). The assessment of observers also shows higher scores for images with contrast compared to images without contrast.Conclusions: The 3D NerveVIEW sequence combined with gadolinium contrast improved vascular suppression, increased the contrast between pelvic nerves and surrounding tissue, and enhanced the visualization of nerves and their branches. This study may be helpful for the technically challenging preoperative planning of pelvic diseases surgery.